THE SPHERE CRITICALITY PROBLEM FOR SPECIFIED ISOTROPIC SCATTERING MODEL - ALCAN, E; YILDIZ, C (EDITRICE COMPOSITORI BOLOGNA, 1992)
In this article, the variation of the critical radius in the monoenergetic-neutron transport theory has been studied. The F(N) method is used to solve the critical problem, for the case of specified isotropic scattering. Exact numerical results are obtained and tabulated for selected illustrative cases. The results indicate that the critical radius increases with increasing forward anisotropic scattering.
Keywords: TRANSPORT PROCESSES, THEORY; NEUTRON PHYSICS; NEUTRON-TRANSPORT THEORY; FN METHOD; BACKWARD; SLAB; Physics